Removal of failed permanent makeup: laser and non-laser methods, risks and prospects - Saburkina, Oleksandra (Global Prosperity, 2025)
Abstract. The article is devoted to the analysis of modern laser and non-laser methods of removing failed permanent makeup, their risks, effectiveness and potential development directions. The purpose of the article is to investigate methods of removing permanent tattoos using laser and non-laser methods. In the course of the scientific research, general scientific methods of cognition were used: analysis, synthesis, induction, deduction, comparison, classification, generalization, systematization of scientific sources. The results of the study show that in clinical practice the leading approach to removing failed permanent makeup is the use of Q-switched lasers. The main types of lasers, such as ruby (694 nm), Nd:YAG (1064 and 532 nm), are reviewed. It is shown that these systems are based on the photoacoustic effect, in which pigment particles are destroyed under the influence of short pulses with subsequent removal through the immune system. It is shown that fractional lasers (ablative and non-ablative) also have applications as additional or combined tools, especially when working with resistant areas. The effectiveness and dangers of non-laser methods, such as dermabrasion, salabrasion and chemical removal using trichloroacetic acid and phenol, are separately investigated. It is shown that prospects in this area are associated with the development of combined protocols that combine laser fragmentation of the pigment with subsequent purification (fractional, chemical or mechanical), as well as taking into account the nanoscale characteristics of dyes for more accurate selection of laser exposure parameters. The practical significance of the study lies in the generalization of the evidence base for choosing the optimal tactics for removing unsuccessful permanent makeup in clinical dermatology and aesthetic medicine.